2005
DOI: 10.1016/j.lfs.2005.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nor-trimebutine on neuronal activation induced by a noxious stimulus or an acute colonic inflammation in the rat

Abstract: To cite this version:Valérie Sinniger, Patrick Mouchet, Bruno Bonaz. Effect of nor-trimebutine on neuronal activation induced by a noxious stimulus or an acute colonic inflammation in the rat.. Life Sciences, Elsevier, 2005, 77 (23) EFFECT OF NOR-TRIMEBUTINE ON NEURONAL ACTIVATION INDUCED BY A NOXIOUS STIMULUS OR AN ACUTE COLONIC INFLAMMATION IN THE RATValérie Sinniger(1,2), Patrick Mouchet (1), and Bruno Bonaz (1,2) ABSTRACTNor-trimebutine is the main metabolite of trimebutine which is used in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…This active metabolite acts as a blocker of sodium channels activity and also has a potent local anaesthetic effect (Roman et al., ). In rats, it decreases c‐Fos expression in the thoracolumbar and lumbo‐sacral spinal cord in laminae I, II, V, VII and X, possibly explaining the antinociceptive effects against abdominal pain in IBS (Sinniger et al., ). With the addition of a H 2 S‐releasing moiety to trimebutine, additional effects and mechanisms of action are to be expected with the GIC‐1001 compound.…”
Section: Discussionmentioning
confidence: 99%
“…This active metabolite acts as a blocker of sodium channels activity and also has a potent local anaesthetic effect (Roman et al., ). In rats, it decreases c‐Fos expression in the thoracolumbar and lumbo‐sacral spinal cord in laminae I, II, V, VII and X, possibly explaining the antinociceptive effects against abdominal pain in IBS (Sinniger et al., ). With the addition of a H 2 S‐releasing moiety to trimebutine, additional effects and mechanisms of action are to be expected with the GIC‐1001 compound.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that remodelling of CNS nociceptive networks is largely responsible [84][85][86] though until recently, this has been relatively unexplored in models of visceral inflammation. Immunohistochemistry (IHC) has been employed to investigate the properties of spinal cord and brainstem neurons during and after visceral inflammation 29,[33][34][35]45,46,48,63,64,68,75,77,79,80,[86][87][88][89][90][91][92][93][94][95][96][97] . This approach is based on the premise that structural remodeling of neural networks in the CNS underlies the exaggerated reflex behaviors observed after visceral inflammation [84][85][86] .…”
Section: Anatomical/molecular Approachesmentioning
confidence: 99%
“…Most used c-Fos (20%), and expression of either marker was consistently increased 29,[33][34][35]45,63,64,68,80,[86][87][88]90,[92][93][94]96,97 . Neural activation was maximal in spinal cord segments T13-L1 and L6-S2 in models of colitis [33][34][35]45,48,63,86,87,93,94,96,97 , T3-L1 in pancreatitis 64,68,80,88,90,92 and T6 for gallbladder inflammation 29 . Labeling was observed in lamina I-VII and/or X, reflecting the diffuse termination of visceral afferents in the spinal cord compared to their cutaneous counterparts 29,[33][34][35]45,63,64,68,80,[86][87]…”
Section: Markers Of Neural Activationmentioning
confidence: 99%
“…The muscarinic acetylcholine receptor plays a crucial role in afferent bladder activation that enhances detrusor overactivity in spinal cord-injured rats ( Matsumoto et al, 2012 ), but this effect does not influence regeneration after spinal cord injury, so it is unlikely to be relevant for the observations in the present study. The trimebutine metabolite nor-trimebutine was shown to decrease Fos activation in the spinal cord and the sacral parasympathetic nucleus after chronic inflammation and this effect was suggested to underlie the decrease of abdominal contractions and abdominal pain after trimebutine treatment ( Sinniger et al, 2005 ). However, it was also suggested that activation and upregulation of Fos might be necessary for regeneration after SCI ( Sabin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%